Enhancing the Oncolytic Efficacy of Vaccinia Virus by Mutagenic Augmentation of EEV Production - Laporte, Aimée N. (Université d'Ottawa / University of Ottawa, 2012)
Oncolytic viruses are currently under investigation as anti - cancer therapies due to their innate ability to selectively infect and destroy cancer cells. Major barriers to this anti - tumour effect include inefficient viral spread and immune - mediated neutralization. This study aims to overcome these limitations by taking advantage of the life cycle of the oncolytic clinical candidate known as vaccinia virus (VACV). Naturally, a small proportion (<1%) of VACV progeny are released from infected cells with a cell - derived membrane and become known as extra - cellular enveloped virus (EEV). Due to this additional membrane, EEV can be shielded from many anti -viral immune factors , allowing it to travel further and largely avoid host - mediated neutralization. This form of VACV is important for long range virus dissemination as well as sustained infection. Though the exact mechanism remains to be elucidated, it has been demonstrated that EEV release can be influenced by Abl tyrosine kinase (Abl TK) function. Specific point mutations in viral envelope proteins are known to bring about enhanced viral release, resulting in an elevated proportion of produced EEV. In this study, we investigate the effect of EEV enhancing modifications within various oncolytic VACV strains. Our data reveals that this augmentation of EEV production through the A34R L151E mutation within the Copenhagen (Cop) backbone can enhance the oncolytic potential of VACV in vivo through enhanced spread and immunoevasion.
Keywords: Oncolytic Virus; EEV; Vaccinia Virus